Open Innovation Practice: A Case Study of University Spin-Offs - Yuliya Shutyak (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The paper investigates the practice of Open Innovation (OI) of university spin-offs. Three interviews were conducted to discuss the knowledge of spin-offs about OI, their attitude to this innovation management strategy based on perceived advantages and disadvantages, and their motivation towards OI practice in the future. Problems with planning, control and trust appear to be some of the most important for OI success. Focusing on these and other urgent aspects of OI, the article discusses a research agenda that can help in formulating research questions and hypothesis, thus directing their efforts to search for solutions to identified problems